2018
DOI: 10.1038/s41598-018-20597-6
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-degrading enzyme is not secreted from cultured cells

Abstract: Insulin-degrading enzyme (IDE) functions in the catabolism of bioactive peptides. Established roles include degrading insulin and the amyloid beta peptide (Aβ), linking it to diabetes and Alzheimer’s disease. IDE is primarily located in the cytosol, and a longstanding question is how it gains access to its peptide substrates. Reports suggest that IDE secreted by an unconventional pathway participates in extracellular hydrolysis of insulin and Aβ. We find that IDE release from cultured HEK-293 or BV-2 cells rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…Of note, a certain enzymatic activity is detected associated to the presence of IDE protein in EVs, although to the same extent that the intracellular IDE activity displayed by cholesterol-enriched cells exposed to Aβ, which is significantly low compared to untreated cells. Neither IDE presence nor endopeptidase activity is observed in EVs isolated from untreated control cells, in agreement with a recent article that questions the release of IDE in cultured cells [60]. Moreover, and unlike cholesterol-mediated alterations of IDE function, the release of IDE through EVs after cellular cholesterol enrichment does not require Aβ exposure.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, a certain enzymatic activity is detected associated to the presence of IDE protein in EVs, although to the same extent that the intracellular IDE activity displayed by cholesterol-enriched cells exposed to Aβ, which is significantly low compared to untreated cells. Neither IDE presence nor endopeptidase activity is observed in EVs isolated from untreated control cells, in agreement with a recent article that questions the release of IDE in cultured cells [60]. Moreover, and unlike cholesterol-mediated alterations of IDE function, the release of IDE through EVs after cellular cholesterol enrichment does not require Aβ exposure.…”
Section: Discussionsupporting
confidence: 88%
“…This process is stimulated by statins which might be a contributory factor in the proposed protection against AD development by statin treatment (Glebov & Walter, ). A recent study has, however, now called into question the significance of IDE secretion from cells suggesting that the presence of extracellular IDE is largely a reflection of a loss in cell integrity (Song, Rodgers, & Hersh, ), and hence, the relevance of IDE to extracellular peptide degradation in vivo may require some reevaluation. Nevertheless, the evidence for a significant involvement of IDE in Aβ clearance in vivo remains strong as does its potential as a therapeutic target in AD prevention.…”
Section: The Key Adesmentioning
confidence: 99%
“…According to Yin et al (2006), in addition to NEP, ECE, and IDE, there may be proteases that have yet to be experimentally identified, contributing to astrocytemediated degradation of Aβ, because NEP, ECE, and IDE were undetected with Western blot analysis of conditioned media of neonatal mouse astrocytes. Moreover, it has been reported that cultured cells may be incapable of secreting IDE, and it is still undetermined whether NEP is capable of degrading oligomeric amyloid beta (Saido and Leissring, 2012;Song et al, 2018). There is evidence that estrogen promotes amyloid beta degradation through the induction of NEP (Liang et al, 2010), and there is also evidence that IDE is induced by 17β-estradiol, reducing amyloid beta load in vivo (Zhao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%